TRANSFORMATION OF THE CONCEPT "SUBJECT" IN THE CLINICAL DISCOURSE OF PHILOSOPHICAL ANTHROPOLOGY - V. M. Skyrtach (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose is the post-metaphysical conceptualization of the subject in the clinical discourse of philosophical anthropology. Theoretical basis of research combines the means of discursive analytics and the general principles of historical and philosophical science. The logic of the research coincides with the paradigmatic understanding of the subject’s transformations and suggests a transition from diagnostic strategies of the analysis of individual being as the basis of the pathological nature of the subject to the study of therapeutic models of communication as the determinants of pathology and, finally, to the analytics of the subject in the horizon of polysubject sociality.Originality of the work consists in disclosing the basic anthropological models of the subject, corresponding to the functions of diagnosis and therapy. It is shown that, in spite of the revolutionary nature of certain projects, which allows them to be classified as postmetaphysical, they still have relapses of metaphysics existing in the image of the subject, which is conceived as the basis of authenticity. According to the criteria for practical implementation, the key is the transformation of the theories of the subject oriented toward self-determination and autonomy into concepts focused on responsibility, caring for what exists and how to exercise it as a person. Conclusions. The research proved that the image of the postclassical subject focused on the ideal of his own authenticity should be diagnosed as pathological. It showed that the accentuation is purely inexpedient in terms of discursiveness, conversation, and the result is the assertion of the independence of the internal, albeit marginal, world of the deviant subject. There is grounded the necessity of bringing the problem to the logic of social interaction, which raises the semantic phenomena organization form that is normal structure of the vital world; on its basis a full-fledged subject emerges with ideas about his own self-sufficiency, and concern for what exists.